Navigating the complexity of ecological stability - Mike Fowler (Ecology Letters, 2016)
Human actions challenge nature in many ways. Ecological responses are ineluctably complex, demanding measures that describe them succinctly. Collectively, these measures encapsulate the overall ‘stability’ of the system. Many international bodies, including the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services, broadly aspire to maintain or enhance ecological stability. Such bodies frequently use terms pertaining to stability that lack clear deﬁnition. Consequently, we cannot measure them and so they disconnect from a large body of theoretical and empirical understanding. We assess the scientiﬁc and policy literature and showthat this disconnect is one consequence of an inconsistent and one-dimensional approach that ecologists have taken to both disturbances and stability. This has led to confused communication of the nature of stability and the level of our insight into it. Disturbances and stability are multi-dimensional. Our understanding of them is not. We have a remarkably poor understanding of the impacts on stability of the characteristics that deﬁne many, perhaps all, of the most important elments of global change. We provide recommendations for theoreticians, empiricists and policy-makers on how to better integrate the multidimensional nature of ecological stability into theirresearch, policies and actions.